2022
DOI: 10.3390/life12081229
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Immune-Monitoring System for Immune Checkpoint Inhibitors

Abstract: Immune checkpoint inhibitors (ICIs) have a major impact on cancer treatment. However, the therapeutic efficacy of ICIs is only effective in some patients. Programmed death ligand 1 (PD-L1), tumor mutation burden (TMB), and high-frequency microsatellite instability (MSI-high) are markers that predict the efficacy of ICIs but are not universally used in many carcinomas. The gut microbiota has received much attention recently because of its potential to have a significant impact on immune cells in the cancer micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…TMB and MSI are the potential predictors of the response to ICB therapy. 29 STEAP3 expression and TMB were positively correlated in THYM, LGG, STAD, KIRC, PAAD, ACC, READ, and TGCT and negatively correlated in PRAD, LUAD, and OV (Figure 3C ). STEAP3 expression and MSI were positively correlated in STAD, BRCA, and LUSC and negatively correlated in READ and PRAD (Figure 3D ).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…TMB and MSI are the potential predictors of the response to ICB therapy. 29 STEAP3 expression and TMB were positively correlated in THYM, LGG, STAD, KIRC, PAAD, ACC, READ, and TGCT and negatively correlated in PRAD, LUAD, and OV (Figure 3C ). STEAP3 expression and MSI were positively correlated in STAD, BRCA, and LUSC and negatively correlated in READ and PRAD (Figure 3D ).…”
Section: Resultsmentioning
confidence: 95%
“…cBioPortal database analysis showed that missense mutations were the main type of STEAP3 gene mutations in pan‐cancer (Figure 3B). TMB and MSI are the potential predictors of the response to ICB therapy 29 . STEAP3 expression and TMB were positively correlated in THYM, LGG, STAD, KIRC, PAAD, ACC, READ, and TGCT and negatively correlated in PRAD, LUAD, and OV (Figure 3C).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Immune checkpoints are hijacked by tumors to reduce T-cell immune responses and evade immune surveillance (9). Despite the groundbreaking success of immunotherapy with antibodies against immune checkpoints such as cytotoxic T-lymphocyteassociated protein 4 (CTLA-4), programmed cell death protein 1 (PD-1), and programmed death-ligand 1 (PD-L1) in multiple solid malignancies (10)(11)(12)(13), pancreatic cancer remains treatment refractory (14)(15)(16). Studies carried out on the effectiveness of ICI treatments involving the use of anti-PD-1 or anti-CTLA-4 antibodies in pancreatic cancer, both alone and in combination, have revealed unsatisfactory overall response rates of 0% and 3%, respectively (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, further improvement in the efficacy of ICIs is necessary. The expression of PD-L1 molecules, high-frequency microsatellite instability, and tumor mutation burden have been identified as potential predictive biomarkers of the therapeutic response to ICIs; however, no definitive factors have been reported to correctly predict the treatment response to ICIs ( 16 ). Therefore, superior predictive biomarkers with high therapeutic efficacy and prognostic value are urgently needed.…”
Section: Introductionmentioning
confidence: 99%